Near-infrared optical imaging of nucleic acid nanocarriers in vivo - Rome, Claire (Methods Mol Biol, 2013)
Non-invasive, real time optical imaging methods are particularly well suited for the in vivo follow up of the distribution of nucleic acids nanocarriers, their dissociation and finally the resulting gene expression or inhibition. Indeed, most small animal imaging devices are performing bioluminescence and fluorescence measurements without moving the animal, allowing a simple, rapid and cost effective method of investigation of several parameters at a time, in longitudinal experiments that can last for days or weeks. Here we propose to help the reader choosing adapted near-infrared (NIR) fluorophores or pairs of fluorophores for FRET assays, reporter genes as well as nanocarriers for in vivo gene and siRNA delivery. In addition, we present the labeling methods of these macromolecules, and of their payload and the protocols to detect them using bioluminescence and NIR fluorescence imaging in mice.